The Tumor Microenvironment of Oral Squamous Cell Carcinoma: Cellular Components and Their Therapeutic Targets - Natalia Tjingson; Muhammad Ihsan Rizal; Ferry Sandra (Molecular and Cellular Biomedical Sciences, 2026)
Advances in genomic and molecular studies have provided new insights into the complex interactions among various components in the tumor microenvironment (TME) that contributes to cancer growth. Oral squamous cell carcinoma (OSCC), the most common subtype of oral cancer, is characterized by its aggressive local invasion, high recurrence rates, and resistance to conventional therapies. Several alterations in TME, such as hypoxia, acidic environment, and increased tissue stiffness, that were caused by tumor-associated altered mechanism of each of its components, further enchance the malignant properties in tumor cells. Despite these findings, no study to date has comprehensively compiled their effects within a single article, thereby limiting the development of integrative conceptual frameworks capable of generating new hypotheses for optimizing anticancer therapies, particularly in OSCC, that target TME components. This study examines the effects of various TME components, their reciprocal interactions, and their intercorrelation with cancer cells, as well as their collective influence on the dynamic interplay within. This study employed a narrative literature review design to identify relevant studies published between 2015 and 2025 in PubMed, Google Scholar, and ScienceDirect databases. Peer-reviewed international studies investigating specific microenvironmental components, associated molecular mechanisms, and therapeutic implications were included. The articles were categorized into two major sections: those addressing cellular components of the TME, followed by therapeutic targets associated with each component and their potential application as anticancer therapies. Coordinated interactions among cellular components, including tumor-associated macrophages, T lymphocytes, cancer-associated fibroblasts, and natural killer cells, together with non-cellular mediators such as extracellular vesicles, shape a highly dynamic tumor microenvironment in oral cancer that regulates tumor progression, immune responses, and therapeutic sensitivity. These findings underscore the need for personalized therapeutic strategies and the integration of TME-based biomarkers to improve precision and durability of OSCC treatment.Keywords: tumor microenvironment, oral cancer, cancer therapy